2008
DOI: 10.4067/s0718-58392008000300012
|View full text |Cite
|
Sign up to set email alerts
|

Paclobutrazol for Height Control of Petunias

Abstract: The effects of paclobutrazol on the height of Petunia × hybrida hort. ex E. Vilm. were studied. An experiment on 'Bravo F1' was performed at the National Institute for Agricultural Technology (INTA), San Pedro Agricultural Experimental Station (33º4' S, 59º4' W), Buenos Aires Province, Argentina, in the spring of 2006. Treatments consisted of three colours of flower (white, red and blue), four concentrations of paclobutrazol by irrigation (0, 5, 10 and 15 mg L -1 and three application times (at 10-12, 18-20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A delay was observed in some Iris cultivars in the visible appearance buds in plants treated with PBZ (Francescangeli, 2009). The application of PBZ delayed the appearance of the flower color in Petunia (Francescangeli and Zagabria, 2009). Flurprimidol application caused flowering delay of Ornithogalum saundersiae (Salachana and Zawadzińska, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…A delay was observed in some Iris cultivars in the visible appearance buds in plants treated with PBZ (Francescangeli, 2009). The application of PBZ delayed the appearance of the flower color in Petunia (Francescangeli and Zagabria, 2009). Flurprimidol application caused flowering delay of Ornithogalum saundersiae (Salachana and Zawadzińska, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…and Nicotiana alata Link & Otto have become popular annual bedding ornamental plants and economically profitable potted plants cultivated in different growth substrates in greenhouses. Petunias belong to the Solanaceae family and are used in landscape, private garden, and building decoration (Dole and Wilkins, 2004;Arancon et al, 2008;Francescangeli and Zagabria, 2008;Xu et al, 2010), pharmaceutical and cosmetics industry, and phytoremediation (Watharkar et al, 2013). Nicotiana alata (ornamental tobacco) has a good potential for commercial horticulture and is also used in pharmacy or to provide antifungal substances for pathogens control (Gaspar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The highest dose of PBZ extended flower longevity by 2.5 days relative to the control. FRANCESCANGELI & ZAGABRIA (2008) reported increased floral longevity of petunia with PBZ doses; however, SINGH et al (2016) observed reduced floral longevity of geraniums. According to OLSEN & ANDERSEN (1995), growth retardants generally reduce flower longevity, but it depends on the dose, species, and the retardant.…”
Section: Resultsmentioning
confidence: 98%